Rescue of respiratory failure in pulmonary alveolar proteinosis due to pathogenic MARS1 variants - Lenz, Dominic; Stahl, Mirjam; Seidl, Elias; Schöndorf, Dominik; Brennenstuhl, Heiko; Gesenhues, Florian; Heinzmann, Tina Maria; Longerich, Thomas; Mendes, Marisa I.; Prokisch, Holger; Salomons, Gajja S.; Schön, Carola; et al. (Pediatric pulmonology, 2020)
Background Pulmonary alveolar proteinosis (PAP) is a heterogeneous condition with more than 100 different underlying disorders that need to be differentiated to target therapeutic options, which are generally limited. Methods The clinical course of two brothers with pathogenic variants in the methionyl-tRNA synthetase (MARS)1 gene was compared to previously published patients. Functional studies in patient-derived fibroblasts were performed and therapeutic options evaluated. Results The younger brother was diagnosed with PAP at the age of 1 year. Exome sequencing revealed the homozygous MARS1 variant p.(Arg598Cys), leading to interstitial lung and liver disease (ILLD). At 2 years of age, following surgery hypoglycemia was detected, the pulmonary condition deteriorated, and the patient developed multiorgan failure. Six therapeutic whole lung lavages (WLL) were necessary to improve respiratory insufficiency. Methionine supplementation was started and a high protein diet ensured, leading to complete respiratory recovery. The older brother, homozygous for the same MARS1 variant, had a long-known distinct eating preference of methionine-rich food and showed a less severe clinical phenotype. Decreased aminoacylation activity confirmed the pathogenicity of p.(Arg598Cys) in vitro. In agreement with our review of currently published ILLD patients, the presence of hepatopathy, developmental delay, muscular hypotonia, and anemia support the multisystemic character of the disease. Conclusions Catabolic events can provoke a severe deterioration of the pulmonary situation in ILLD with a need for repetitive WLL. Although the precise role of oral methionine supplementation and high protein intake are unknown, we observed an apparent treatment benefit, which needs to be evaluated systematically in controlled trials.
Gesehen am 28.10.2025